The role of ambiance and service in culinary tourism: A case study at D’Warung - Sukartini, Ni Wayan; Kanca, I Nyoman; Budiarta, I Putu; Sumawidari, Ida Ayu Ketut (Journal of Commerce, Management, and Tourism Studies, 2024)
This study examines the culinary and dining experience at D’Warung, a popular restaurant known for its diverse menu and cozy atmosphere. The primary objective is to analyze the restaurant's appeal, focusing on its food offerings, ambiance, and customer service. Data collection was conducted through observation and interviews with staff and customers, assessing factors such as the quality of the food, the level of crowd, and the friendliness of the service. The results reveal that D’Warung stands out for its comfortable atmosphere, friendly staff, and a varied menu that includes both local and western dishes. The analysis highlights these factors as key contributors to the restaurant’s success. In conclusion, the study emphasizes the importance of creating a welcoming environment and providing excellent service in shaping a memorable dining experience.